2014
DOI: 10.4103/0970-9290.135912
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cone beam computed tomography comparison of NovaBone Dental Putty and PerioGlas in the treatment of mandibular Class II furcations

Abstract: Putty form was comparable to particulate form for resolution of Class II furcation defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Similar to previous reports, CBCT analysis in this study has enabled us to volumetrically assess the healing characteristics and regeneration with relatively less invasion. 38,39 Further long-term, multicenter studies with biochemical assays and histologic evaluation for the regenerated tissues should be performed that would advocate and support the outcomes of the combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous reports, CBCT analysis in this study has enabled us to volumetrically assess the healing characteristics and regeneration with relatively less invasion. 38,39 Further long-term, multicenter studies with biochemical assays and histologic evaluation for the regenerated tissues should be performed that would advocate and support the outcomes of the combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Asmita et al . [21] reported HDF in Class II mandibular furcation using two different forms of bioactive glass. The Pearson correlation analysis showed no association between RTL and FA on mean change in V-HOF and Fw when recorded on CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…[21] had utilized CBCT for evaluating and recording above-mentioned parameters of the study. Most studies reported mean percentage defect fill on conventional and digital radiography using computer-aided program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations